Analyzing socioeconomic and regional inequalities in minimum dietary diversity consumption among children aged 6–23 months in Ethiopia: a decomposed concentration index approach - Endawkie, Abel; Kebede, Shimels Derso; Abeje, Eyob Tilahun; Bekele Enyew, Ermias; Daba, Chala; Asmare, Lakew; Bayou, Fekade Demeke; Arefaynie, Mastewal; Mekonen, Asnakew Molla; Tareke, Abiyu Abadi; Keleb, Awoke; Abera, Kaleab Mesfin; et al. (Frontiers in Sustainable Food Systems, 2025)
BackgroundEthiopia faces inadequate minimum dietary diversity (MDD), which significantly contributes to rising death rates and the spread of diseases among children aged 6–23 months. The evidence of socioeconomic and regional inequalities is central to the Sustainable Development Goals (SDGs), and it is especially crucial for guiding the development of local, regional, and national policies and initiatives that address these inequalities in MDD consumption. This will help achieve the SDG target of ending all forms of malnutrition. However, there is limited evidence on socioeconomic and regional inequalities in MDD consumption among children in Ethiopia. Therefore, this study aimed to investigate the socioeconomic and regional inequalities in MDD among children aged 6–23 months in Ethiopia.MethodsThis study utilized nationally representative weighted data comprising 3,145 samples from the 2019 Ethiopia Demographic and Health Survey (EDHS). The concentration index (CIX)was employed to estimate the socioeconomic and regional inequalities in MDD consumption.ResultsThe prevalence of adequate MDD in Ethiopia was 7.11%. The concentration index (CIX) values for MDD by wealth status and region were 0.3 and 0.084, respectively, with a p-value of <0.05 for both. The concentration curve was below the equality line, and adequate MDD was concentrated among the wealthy, developed, and urban regions of Ethiopia. Maternal education (0.88%), the sex of the household head (0.3%), and region (3.1%) contributed to the observed inequalities in MDD across both the poor and wealthy regions. Wealth status (11.06%), maternal age (6.7%), maternal educational status (1.87%), and residence (0.02%) contributed to the observed inequalities in MDD consumption across both the less developed and developed regions of Ethiopia.ConclusionThis study revealed that the wealth and regional inequalities observed in MDD consumption in Ethiopia were influenced by factors such as parental marital status, women’s educational status, place of residence, and short preceding birth intervals. Adequate MDD consumption among the children in Ethiopia was concentrated in the wealthy and developed regions. Therefore, efforts should focus on reducing poverty, improving maternal education, and implementing targeted interventions. In particular, nutrition and public health organizations should support less developed regions to achieve greater dietary diversity for infants and young children.